Rubrics as an evaluation tool in economics (2010)
Critical thinking and writing skills are necessary competencies for effective communication, problem resolution, and analysis in economics. Although there are several different approaches to evaluate critical thinking and writing skills, rubrics is an evaluation tool which provides more information than numerical grades because it establishes a set of criteria which both professors and students know and are able to evaluate jointly. Meanwhile, rubrics provide students more effective feedback about critical aspects of a given course such as the identification of problems, the quality of evidence furnished by the students, accuracy of conclusions, and objective reflection, among